2013
DOI: 10.1097/dcr.0b013e31829c654f
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Human Papillomavirus Genotypes in Anal Cytological and Histological Specimens from HIV-Infected Men Who Have Sex with Men and Men Who Have Sex with Women

Abstract: Anal cancer screening should be offered to all HIV-infected men, regardless of their sexual orientation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 36 publications
3
31
1
1
Order By: Relevance
“…The results were very similar to those published by other authors who had observed the percentage of anal dysplasia with low grade cytology (LSIL) at around 40%, 19% ≥AIN2 lesions and the most-frequently identified HPV16 genotype [23].…”
Section: Discussionsupporting
confidence: 91%
“…The results were very similar to those published by other authors who had observed the percentage of anal dysplasia with low grade cytology (LSIL) at around 40%, 19% ≥AIN2 lesions and the most-frequently identified HPV16 genotype [23].…”
Section: Discussionsupporting
confidence: 91%
“…This was demonstrated by the low number of patients with invalid results from anal cytology (0.5%), as well as the discordant cytological and histological findings (HSIL cytology and absence of histological abnormalities), three (1.4%) (33). Our rate of identification of high-grade histological lesions was similar to that of some other relevant groups (34) and two important studies performed in our country (35,36), the first of which was carried out in one of the largest cities in Spain. The concordance between HSIL cytology and the histological HSIL result has been high, denoting the diagnostic value of this cytological grade (22,37,38).…”
Section: Discussionsupporting
confidence: 56%
“…We used a Carl Zeiss 150FC (Carl Zeiss, Oberkochen, Germany) colposcope for HRA. HR-HPV genotyping was carried out by polymerase chain reaction amplification according to the Cobas 4800 HPV system test (Hoffmann -La Roche Ltd. Rotkreuz, Switzerland), with three TaqMan probes: two specific for the HPV 16 and HPV 18, and another for types 31,33,35,39,45, 51, 52, 56, 58, 59, 66 and 68.…”
Section: Prevalence Study Of Cytological Abnormalities and Hr-hpv Infmentioning
confidence: 99%
“…Previous studies have shown that anal HPV infection are more prevalent among HIV-infected MSM than among HIV-infected MSW (84–85.6% vs 40.8–46%)[29, 30, 33]. HIV-infected MSM also had a higher prevalence of HR-HPV compared with HIV-infected MSW (54–75% vs 18–28%)[31, 32, 34].…”
Section: Discussionmentioning
confidence: 99%